2012
DOI: 10.7744/cnujas.2012.39.1.061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of quercetin on antioxidant activity and meat quality of beef cattle

Abstract: : This study was carried out to investigate the effects of dietary supplementation of quercetin (Kocetin TM , QR)on antioxidative activity and meat quality of beef cattle (Holstein-Friesian). Beef cattle were divided into 3 groups; dietary supplementation of QR at 21 (n=4) and 42 ppm (n=3), and non-supplemented control (n=4). The QR comprised of 10% of quercetin. After slaughtering the beef cattle, loins were obtained and analyzed. Dietary supplementation of QR at 42 ppm showed significantly higher final pH of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…This could be attributed to the similar energy content of the dietary treatments and the similar management and slaughter conditions employed during the trial. The pH values observed in the current study fall within the pH of normal meat as reported in goats [ 1 ] and beef [ 24 ]. The current observation corroborates the findings of Karami et al [ 5 ] who observed that dietary Andrographis paniculata and turmeric powder had no effect on muscle pH in chevon.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This could be attributed to the similar energy content of the dietary treatments and the similar management and slaughter conditions employed during the trial. The pH values observed in the current study fall within the pH of normal meat as reported in goats [ 1 ] and beef [ 24 ]. The current observation corroborates the findings of Karami et al [ 5 ] who observed that dietary Andrographis paniculata and turmeric powder had no effect on muscle pH in chevon.…”
Section: Discussionsupporting
confidence: 87%
“…The current observation corroborates the findings of Karami et al [ 5 ] who observed that dietary Andrographis paniculata and turmeric powder had no effect on muscle pH in chevon. Contrarily, dietary supplementation of quercetin increased the pH of longissimus muscle in Holstein Friesian cattle [ 24 ]. Postmortem storage influenced muscle pH in Dorper lambs.…”
Section: Discussionmentioning
confidence: 99%
“…This last parameter, the final pH value in meat, is closely related to the antemortem glycolytic potential because a low glycolytic potential has been observed in other studies of antioxidants and has resulted in an increase in pH [133]. In contrast to the results observed by previous authors, Yang et al [134], Hong et al [90], Zhou et al [110], Kang et al [130], Rossi et al [112] and Goliomytis et al [98] reported similar effects between phytochemical treatments and control diets on color parameters, shear force, cooked weight loss, fat content, pH, drip loss, and WHC.…”
Section: Meat Qualitymentioning
confidence: 97%
“…The water holding capacity (WHC) was determined by centrifugation method of Kang et al (2012). Briefly…”
Section: Physicochemical Propertiesmentioning
confidence: 99%